Influence of the catBCE sequence on the phenotypic reversion of a pcaE mutation in Acinetobacter calcoaceticus. - Doten, R C (1987)
Isofunctional beta-ketoadipate:succinyl coenzyme A transferases I and II are encoded by the pcaE and catE genes, respectively, of Acinetobacter calcoaceticus. The genes are under separate transcriptional control and genetically unlinked. Mutations in the pcaE gene result in a p-hydroxybenzoate-negative (POB-) phenotype, whereas catE mutations cause a benzoate-negative (Ben-) phenotype. A. calcoaceticus ADP125 carries the pcaE3125 mutation and gave rise to POB+ revertants with a frequency of 10(-4). A 5.0-kilobase-pair (kb) EcoRI restriction fragment containing the catBCDE genes possesses two SalI restriction sites separated by 1.5 kb. Removal of the DNA between the SalI sites created a deletion removing the terminal 35 base pairs of the catB gene, the 300-base-pair catC gene, and about 1.1 kb of the 1.2-kb catE gene. Transformation of strain ADP125 with the modified EcoRI fragment lacking the SalI segment produced natural transformants containing this designed deletion with a frequency of 20%. The frequency of POB+ phenotypic reversion of the pcaE3125 mutation in these transformants was more than 300-fold lower than the frequency of phenotypic reversion observed in genetic backgrounds containing the catBCE segment. Alleles created by pcaE phenotypic reversion in a wild-type cat genetic background were unlinked to the cat gene cluster, and revertant transferases were expressed inducibly with the pca genes. Alterations in the restriction pattern of the pca gene cluster in several revertants were observed, indicating that multiple sequence changes have occurred in the pca genes during reversion. Growth of the phenotypic revertants under nonselective conditions resulted in loss of either the POB+ phenotype or both the POB+ and Ben+ phenotypes at high frequency. Southern hybridizations revealed that loss of the POB+ of Ben+ phenotype was due to deletion of the entire pca or cat gene cluster, a loss of at least 16 kb in some strains. Revertants isolated in a catBCE deletion background were stable. These results suggest that enhanced phenotypic reversion of pcaE3125 in wild-type cat background is due to repair of the mutation by recombination between the catBCE and pcaE3125 sequences. Genetic instability of the phenotypic revertants may be attributed to deletion of pca and cat sequences by recombination between regions of homology created as a consequence of pcaE repair.